Winter Survival of Experimental Bermudagrasses in the Upper Transition Zone - Mingying Xiang; Jack Fry; Yanqi Wu (Kansas Agricultural Experiment Station Research Reports, 2019)
A winter with very cold temperatures in 2017–2018 allowed for good separation of standard and experimental bermudagrasses for freezing tolerance. When evaluated in May 2018, survival of commonly used cultivars was: Tifway, 0%; Latitude 36, 20%; Northbridge, 25%. Some experimental progeny had up to 98% winter survival on the same rating date.
Keywords: bermudagrass; turfgrass; cold hardiness